TOWARDS A REDEFINITION OF THE RIGHT TO WORK FOUNDATIONS: from "free work" to solidarity decolonial work - D'Angelo, Isabele Banderia de Moraes; Pimentel, Boris Marañón (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2018)
This article aims to criticize the theoretical elements whichconcerns the right to work, assuring that work has been wrongly misunderstood with salaried work or "free" work, as opposed to servile work whichtook place in Europe until the emergence of the industrial capitalism. Salaried work is only one of the historical forms of labor control and although it is not subject to extra-economic coercion, such as the servile labor, it daily experiences despotism and alienation in the capitalist labor organization. In face of such situation, this article proposes a resignification of the labor conceptin order to incorporate other modalities with solidarity and horizontal features that have emerged in this historical period of expansion of structural unemployment,as well as the hegemony of finance capital.